1996
DOI: 10.1046/j.1365-2265.1996.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoparathyroidism and insulin‐dependent diabetes mellitus in a patient with Kearns–Sayre syndrome harbouring a mitochondrial DNA deletion

Abstract: We report a 17-year-old girl with short stature, external ophthalmoplegia, atypical retinal pigmentary degeneration, sensorineural hearing loss, and cardiac conduction defect (Kearns-Sayre syndrome). A large-scale deletion (6741 base pairs) in mitochondrial DNA was found in her muscle specimen. She also had insulin-dependent diabetes mellitus (IDDM). On admission, her plasma glucose level was elevated at 31.0mmol/l with mild ketoacidosis, and haemoglobinA1c elevated at 16.5%. After improvement of diabetic keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Thirteen reports were single patient cases with various clinical presentations. 8,9,11,15,16,[22][23][24][25][26][27][28][29] One report had 4 patients with hypoparathyroidism, 17 another had 7 patients with KSS, 3 one had 3 patients with Pearson syndrome, 14 one had 2 patients with multiple endocrine problems, 6 and another had 20 KSS patients. 19 Overall, 34 patients had typical KSS, CPEO, or MM, 14 patients had multisystemic disorders with initial presentation of non-neural, nonmuscular clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen reports were single patient cases with various clinical presentations. 8,9,11,15,16,[22][23][24][25][26][27][28][29] One report had 4 patients with hypoparathyroidism, 17 another had 7 patients with KSS, 3 one had 3 patients with Pearson syndrome, 14 one had 2 patients with multiple endocrine problems, 6 and another had 20 KSS patients. 19 Overall, 34 patients had typical KSS, CPEO, or MM, 14 patients had multisystemic disorders with initial presentation of non-neural, nonmuscular clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mtDNA deletion syndromes have been reported in patients with various clinical manifestations, including Addison disease, 6 -8 atypical Pearson presentation, 9 -11 cyclic vomiting, 6,9,12 severe renal tubulopathy, 11 hepatic dysfunction, 13 dysarthria, 9,10 organic acidopathy, 14,15 and hypoparathyroidism and hypocalcemia. 6,16,17 The mitochondrial DNA deletion syndrome is defined as any case with a single mtDNA deletion, regardless of the clinical phenotype. In KSS, deleted mtDNA occurs mainly in muscle and not always in leukocytes.…”
mentioning
confidence: 99%
“…Magnesium depletion may lead to hypoparathyroidism either by suppression of PTH secretion or production of ineffective circulating hormone [8]. However, in our case even though magnesium depletion was partially improved, PTH levels remained extremely low.…”
Section: Discussionmentioning
confidence: 51%
“…Mitochondrial biochemical derangements may trigger the onset of this dysfunction by reducing ATP production; an autoimmune etiology has also been implicated but not strongly enough supported [2]. Moreover, of 2 autopsied hypoparathyroid cases with KSS, 1 had absent glands while in the other only one gland could be identified by microscopic examination [8]. No study showed evidence of dietary, malabsorption or metabolic vitamin D disorders or autoimmune mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…The parathyroid gland may also be vulnerable to mutations in mtDNA because its function requires a high energy supply. In fact, idiopathic hypoparathyroidism has been described in another mitochondrial encephalomyopathy, Kearns-Sayre syndrome (14)(15)(16)(17), as well as in diabetic patients with an A3243G mutation of mtDNA (18,19 may also be necessary to examine mutations in the mtDNAof individuals with idiopathic hypoparathyroidism, especially those with a family history of the disease and/or with diabetes mellitus or impaired hearing.…”
Section: Discussionmentioning
confidence: 99%